Condições de trabalho do profissional de secretariado executivo no setor público: um estudo de caso na Universidade Federal do Ceará - Pinheiro, Valdênia Ferreira (2012)
This study examines the working conditions of Executive Secretaries at the Federal University of Ceará (UFC). Interest in this problem stems from the need to understand the impacts to workers after the changing world of work demanded by phenomena such as globalization and neoliberalism, where the public sector, inserted in this context, also suffers the consequences of this new world order being pressured to conform to existing models. Specifically for the professional executive secretarial, are required new knowledge and new requirements, and, in many situations, the conditions necessary for the completion of this work is not satisfactory. Thus, the objective of this study was to analyze the conditions - objective and subjective - the work of professional executive secretarial work at the Federal University of Ceará (UFC). The especifics objectives were defined to characterize the profile of the executive secretaries at the institution; analyze the objective conditions regarding ergonomic hazards and physical infrastructure, and to analyze the subjective aspects such as the degree of autonomy, participation in decision making and recognition, and others. This research uses in its theoretical, studies by Antunes (2007), Harvey (2005), Alves (1997),Nonato Jr. (2009), Iida (2005), among others. The research is based on the goals classified as exploratory and descriptive, based on technical procedures classified as a case study using the questionnaire for data collection. This questionnaire was divided into three parts: 1. Asked to characterize the professional profile 2. Closed questions about the objective and subjective conditions, presented through a Likert scale consisting of five response items, and 3. Open question about the working conditions. To present the data we have used descriptive statistics and the results were demonstrated by graphs. The survey results reveal a context where the working conditions of Executive Secretaries, especially with respect to physical infrastructure, are considered satisfactory in the opinion of professionals, however, some aspects that affect the subjectivity of these professionals need to be observed, especially with relation to interpersonal relationships and lack of recognition and appreciation by the institution.